2021
DOI: 10.3390/plants10112533
|View full text |Cite
|
Sign up to set email alerts
|

Barley Genotypes Vary in Stomatal Responsiveness to Light and CO2 Conditions

Abstract: Changes in stomatal conductance and density allow plants to acclimate to changing environmental conditions. In the present paper, the influence of atmospheric CO2 concentration and light intensity on stomata were investigated for two barley genotypes—Barke and Bojos, differing in their sensitivity to oxidative stress and phenolic acid profiles. A novel approach for stomatal density analysis was used—a pair of convolution neural networks were developed to automatically identify and count stomata on epidermal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 74 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…The results of research by [27] show that stomata characters are species-specific. And can be influenced by genetic and environmental changes such as light and CO2 concentration in the atmosphere [28] or land type [30]. Stomata function for the process of transpiration in plants, while the main function of leaf stomata is the exchange of gases needed by plants for the process of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The results of research by [27] show that stomata characters are species-specific. And can be influenced by genetic and environmental changes such as light and CO2 concentration in the atmosphere [28] or land type [30]. Stomata function for the process of transpiration in plants, while the main function of leaf stomata is the exchange of gases needed by plants for the process of photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Higher air humidity with considerable dry soil can trigger stomata opening (Driesen et al, 2020). Previous studies also revealed that stomatal characters were species-specific (Zhang et al, 2012) and affected by both genetic and environmental changes such as light and CO2 concentration in the atmosphere (Hunt et al, 2021) or land type (Sun et al, 2021). Analysis of variance showed that the number of leaves was significantly affected by independent G×L interaction , while chlorophyll content (SPAD value) was significantly affected only by genotypic factors regardless of location (Table 4).…”
Section: Analysis Of Variancementioning
confidence: 86%
“…Nevertheless, the possible presence of other LMWA with strong antioxidant activity in extracts cannot be excluded. Interestingly, in plant organs most exposed to UV-B radiation, the synthesis of HCA derivatives declines in favor of flavonoids [ 80 , 81 ], even though HCAs absorb UV-B more efficiently than flavonoids [ 82 ] and accumulation of HCAs is associated with higher tolerance of oxidative stress among barley genotypes [ 83 ]. As shown in Arabidopsis, acylation of some PheCs (such as saiginols) may enhance their UV-B absorption properties, which confers a fitness advantage to plants that produce them following exposure to prolonged UV-B [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%